The demise of corporate insolvency law in India - van Zwieten, K (2012)
The subject of this thesis is the operation of corporate insolvency law in post-colonial India. Indian corporate insolvency law has been widely condemned as dysfunctional, critics complaining of extreme delays and a series of associated harms to creditors in the disposal of formal proceedings. Surprisingly little is known, however, about why the law has ‘failed’ creditors in this way - why the law operates as it does. That is the question that motivates this thesis. The thesis reports the results of an in-depth study of the introduction and development of India’s two principal insolvency procedures for corporate debtors: liquidation (under the Companies Act 1956) and rescue (under the Sick Industrial Companies (Special Provisions) Act 1985, for industrial companies). The most significant contribution made by the thesis is the reporting of new evidence of the influence of judges on the development of these two insolvency procedures over time, drawn from an original analysis of a large body of Indian case law. This evidence suggests that the role of the courts (or more specifically, the role of judges) has been significantly underestimated in previous attempts to explain the demise of corporate insolvency law in post-colonial India.